Changes in comfort perception and direction change performance of badminton shoes with extensive usage time. (2nd January 2016) - Hong, Youlian; Lam, Wing Kai; Wang, Shaojun; Cheung, Jason Tak-Man
Abstract : This study examined whether the shoe usage time influences the comfort perception and direction change performance of badminton shoes. Fifteen university badminton players performed direction change trials with maximum-effort at new and extensively worn shoe conditions. Two professional badminton shoe models (Shoe Y and Shoe L) were selected to examine if both tested shoes would have similar usage time effect on comfort perception and direction change performance. Comfort perception of in-shoe climate, overall fit, medial-lateral stability, overall cushioning, shoe-ground traction, and overall comfort were measured using a 150 mm Visual Analogue Scales, immediately after the direction change trials. After finishing data collection of new shoe condition (day 1), the tested shoes were assigned to the university badminton team players to simulate the extensively worn condition that normally used during badminton training for eight weeks (i.e., 96 hours in total). The identical testing procedure was performed by the same experimenter for the extensively worn shoe condition (day 2). Paired t -tests were performed to investigate if there were any significant differences between new and extensively worn condition in each of the variables. Significance level was set at P < 0.05. No difference in direction change performance between new and extensively worn conditions was determined in each shoe ( P > 0.05). Y shoe indicated significant poorer perception of medial-lateral stability, overall fit, and in-shoe climate ( P < 0.05) while L shoe indicated significant poorer perception of overall fit and in-shoe climate for the extensively worn shoe condition, compared to the new shoe condition ( P < 0.05). Prolonged shoe usage time plays a role in footwear comfort perception, but not in direction change performance. Changing with a new pairs of shoes would be considered to attain better comfort perception for badminton players during practice and competition.